Amphibious assets of the armed forces of the NATO countries, the Russian Federation and the Republic of China - Kovačević, Nenad V.; Lazić, Goran M. (Vojnotehnički glasnik / Military Technical Courier, 2014)
The article presents a brief overview of modern developments and directions of further development of amphibious assets for overcoming water obstacles in foreign armed forces, notably the amphibian assets of the armed forces of the Parties of the North Atlantic Treaty Organization (NATO), the Russian Federation and the People's Republic of China. The article follows the historical path of the development of amphibious assets.The paper deals with the classification of amphibious assets in foreign armed forces.In preparing the article, there was a big problem to find the latest literature so data from the Internet was largely used. The literature that exists in the Army of Serbia is related to the seventies of the last century, when there was the last investment in amphibious assets.The knowledge on the amphibious assets for overcoming water obstacles in foreign armed forces can be seen as a help in assessing the effects of their use and the need for innovation and investment in  the country’s own resources. Introduction The introduction explains the very concept of water hazard and its characteristics.It also explains the importance of water obstacles in the development of military equipment, but also in terms of the execution of tactical operations and procedures. Historical development of amphibious assets This section shows the historical development of amphibious assets from the early nineteenth century through World War II and Cold War until today.The historical development of amphibious assets is shown through figures 1 to 3. The classification of amphibious assets in foreign armed forces is given as well. Amphibious assets of the armed forces of the NATO countries The amphibious assets of the armed forces of the NATO countries shown here are representative for the armed forces of the NATO countries. The assets of the armed forces of the United States, the United Kingdom, France, Turkey and Germany are given in figures 4 to 11 and explained with their tactical - technical data. Amphibious vehicles of the armed forces of the Russian Federation The amphibious vehicles of the armed forces of the Russian Federation displayed here are representative for the armed forces of the Russian Federation. The displayed assets are just modified versions of the eighties assets, primarily due to the minimal investment of the Russian armed forces into the sector of weapons and equipment. The assets are given in figures from 12 to 18 and explained with their tactical - technical data. Amphibious assets of the armed forces of the People's Republic of China The amphibious assets of the armed forces of the People's Republic of China shown here are representative for the armed forces of the People's Republic of China. Only the original assets of Chinese production are shown since all other assets come from the Russian armed forces. They are shown in Figures 19 and 20 and followed with their tactical - technical data. Conclusion  The conclusion discusses the tendency of further development of amphibious assets in foreign armed forces.
Keywords: amphibious vehicles; armed forces